Haemophilus paragallinarum in chickens in Indonesia : II . Physiological and biochemical properties of Haemophilus spp . from diseased chickens - Sri Poernomo; Sutama .; Yapto Nazrudin (Jurnal Ilmu Ternak dan Veteriner, 1998)
A total of 46 isolates of Haemophilus spp . consisted of 42 local isolates from diseased chickens and four reference strains of Haemophilus paragallinarum were examined for their physiological and biochemical properties . These isolates consisted of 2 groups. One group consisted of 21 local isolates and reference strains of H. paragallinarum were catalase negative and identified as Haemophilus paragallinarum and they did not ferment galactose and trehalose . The other group was catalase positive and suspected as Haemophilus avium . This catalase positive group of these 21 avian Haemophili should be examined with other carbohydrates in order to be identified accurately .   Keywords : Haemophilus spp ., physiological, biochemical, chickens